PENGARUH PANJANG KONDENSOR TERHADAP KINERJA TERMAL THERMOSYPHON - Fina Andika Frida Astuti; Arif Rochman Fachrudin (INFO-TEKNIK, 2019)
Cooling is an important activity in maintaining a large temperature of a component, both mechanical components and electronic components. Component temperature which is maintained from overheating will avoid damage. The cooling process is carried out by moving the heat produced by a component through a heat exchanger. One effective heat exchanger is Thermosyphon. This tool is able to move a number of heat through a very small surface area. Thermosyphon is a pipe that contains a working fluid, consisting of three parts, namely the evaporator section, the adiabatic section and the condenser section. The evaporator has the function of absorbing heat from the heat source and heat is released in the condenser. The process of heat absorption and release of heat is carried out by the working fluid in the pipe, when the fluid is in the heated evaporator it will evaporate towards the condenser the heat is released. The fluid which is finally from the condenser returns to the evaporator. This study aims to determine the thermal performance of the thermosyphon as a heat exchanger with condenser length variations. Thermosyphon is designed with a condenser length variation of 44 cm, 66 cm, 88 cm, 110 cm and 132 cm running with variation temperature. The results showed that, the highest thermal resistance at the shortest condenser length at 400C (140C / W) and the lowest at the longest condenser length at 1200C (10C / W). At all temperatures, all variations in the length of the condenser will increase the output power and heat flux. At the same condenser length, the higher the temperature, the greater the heat flux and output power. The process of this experiment is most effective at the length of the condenser 1.25 (132 cm) from the length of the evaporator length, because after that the value of thermal resistance and output power will experience a permanent tendency.